ANALSISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MASYARAKAT KALIMANTAN SELATAN TERHADAP PENGGUNAAN PEMBAYARAN NON TUNAI - HELMI, RAHMAN; MUBARAK, ZAKI (Islamic Economics and Business Faculty of UIN Antasari, 2014)
Economic growth in Indonesia can not be separated from a strategic role in the payment system to support economic activities. Strategic role of the payment system in economic activities, especially to ensure the implementation of various payment transactions, is made by the public and business. The development of innovations in the payment system is a logical consequence of the growing community needs for existence of instruments and payment mechanisms that are practical, efficient, safe and comfortable. Development of Card Payment Through in South Kalimantan are still very limited in the use of ATM cards, credit cards, and debit cards. The amount of public transactions using credit cards is also relatively very small and generally only in Banjarmasin and Banjarbaru. Card payment through low usage rate is not out of the involvement of the community in adopting card payment, so it is necessary to do research on the characteristics of the community. Characteristics of the community in South Kalimantan that different from other areas will be the research target. It is because people are consumers that determine the development of non-cash payments later. This community preferences will affect the use of non-cash payment instrument towards a cashless society.